HUBUNGAN PEMAHAMAN KONSEP MATEMATIKA BERUPA DIFERENSIAL DAN INTEGRAL DENGAN PEMECAHAN MASALAH FISIKA - Nasution, Febriani Hastini (Institut Pendidikan Tapanuli Selatan, 2018)
The purpose of this research was to know was there any relationship between mathematical concepts understanding of college students in the form of differential and integral with physics problem solving ability in Physical Mathematics subject. The research method was combination methods or mixed methods by sequential explanatory design which combined quantitative and qualitative research method. The research subject was college students in fourth semester of Physics Education Study Program, Education Institute of South Tapanuli. The technique of data collecting was written test, observation, and interview. Based on data analysis obtained there was significant relationship between mathematical concepts understanding of college students in the form of differential and integral with physics problem solving ability in Physical Mathematics subject. This results was proved from correlation coefficient between mathematical concepts understanding of college students (X) with physics problem solving (Y) was with significance 0.000. Based on the decision criteria above so can be concluded that the correlation of the two variables was significant because the significance was smaller than 0.05 (0.000 < 0.05).